ANALISIS LOKASI KRITIS JALUR EVAKUASI PENUMPANG KAPAL PENYEBERANGAN ANTAR PULAU DENGAN METODE PERGERAKAN SIMULTAN - Muhammad, Andi Haris; Paroka, Daeng (FSTPT Indonesia, 2015)
One of important factor to avoid accident fatalities of passanger vessel evacuation is the evacuation route design of safety. A number of critical locations can slow down the evacuation process such as doors, stairs and corridors essential for analysis. This paper discusses a number of critical locations, potential to evacuation failure, especially on ships crossing inter-islands. The method used to identify the critical location or locations where the concentration of passengers during the evacuation process is the Simultaneous Movement Method. The simulation results show that the total time required evacuation of passengers, especially on economy class of KMP Jatra II, since leaving the passenger compartment until all passengers are on the vehicle deck emergency exit is 870 seconds or 14.50 minutes, smaller than required by IMO ( 60 menit). Potential of passenger density or the critical path, starting at the 1st door where in the path traversed by all economy class passengers before entering the 1st and 2nd corridors. Maximum number of passengers that accumulates at these sites is 72 people on 300 seconds. Subsequently passenger’s concentration occurs at the meeting movement toward the passenger emergency exit vehicle deck that is derived from the 3rd and 4th corridors, at the location of a concentration of passengers up to 76 people on 490 second. This study suggests that the potential of location or critical point of the passenger evacuation path occurs at a meeting between two or more evacuation routes, especially in locations such as the transition to the doors, stairs or passenger traffic bottlenecks due to the larger capacity. The results of this analysis can also be used as a basis for determining an alternative evacuation route or routes change if the conditions are experienced during vessel operation.